2022
DOI: 10.3389/fimmu.2022.983581
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal duration of immune checkpoint inhibitors in malignant tumors?

Abstract: Immunotherapy, represented by immune checkpoint inhibitors (ICIs), has made a revolutionary difference in the treatment of malignant tumors, and considerably extended patients’ overall survival (OS). In the world medical profession, however, there still reaches no clear consensus on the optimal duration of ICIs therapy. As reported, immunotherapy response patterns, immune-related adverse events (irAEs) and tumor stages are all related to the diversity of ICIs duration in previous researches. Besides, there lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Furthermore, the optimal duration for IO treatment continues to be a topic of ongoing debate, several trials, including KEYNOTE-189 [ 24 ], KEYNOTE-010 [ 25 ], and CheckMate-153 [ 26 ], suggest the possibility of poor survival outcomes or disease progression after discontinuing IO treatment following one or two years of administration [ 27 ]. Limited research has managed to follow patients who discontinue treatment due to AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the optimal duration for IO treatment continues to be a topic of ongoing debate, several trials, including KEYNOTE-189 [ 24 ], KEYNOTE-010 [ 25 ], and CheckMate-153 [ 26 ], suggest the possibility of poor survival outcomes or disease progression after discontinuing IO treatment following one or two years of administration [ 27 ]. Limited research has managed to follow patients who discontinue treatment due to AEs.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid selection bias, we enrolled patients consecutively, excluding those who had received less than two cycles of treatment. This subgroup represents a considerable proportion of patients with dismal prognoses, and their exclusion may have favorably influenced the evaluation of some correlations [ 52 ]. Furthermore, we were unable to ensure an independent reassessment of the radiology records, resulting in a potential overestimation of objective response rates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the similarity of real-world data to their clinical trial analogues depended on the drug class [ 28 ]. In this study, ICIs may have had prolonged effectiveness after stopping the treatment [ 29 ]; therefore, the PFS might have been longer than the end of treatment in the claims database. EGFR-TKIs are often used beyond progressive disease in patients with NSCLC [ 30 ], and the PFS may therefore be shorter than the DoT.…”
Section: Discussionmentioning
confidence: 99%